Radio La Califata - Monti, Valentina (Italy, 2004)
Duration: 00:33:00 Why the patients of the Clinic for mental diseases in Buenos Aires re-elected Carlos Mehnem for a president without liking him? A documentary on the 2003 presidential elections in Argentine. IN April 2003 Radio La Colifata has organized mock "presidential elections" in a mental clinic in Buenos Airesfor just a day before the official ones. Radio La Colifata, which in Buenos Aires slang means Crazy Radio - was the first radio show in the world to broadcast live from a mental hospital. The founder of the radio, psychologist Alfredo Olivera, had started to use a simple small dictaphone as a speech therapy. More than mere therapy, the show has proven popular with an estimated 12 million listeners. Away from the media limelight, the hospital says the show has had great therapeutic results. Saturday afternoon in Buenos Aires: tucked away behind the towering, prison-like Jose Borda psychiatric hospital, a large group of people is gathering. The Radio La Colifata team are now organizing their own presidential elections. The film provides an idiosyncratic look at the origins of democracy from inside a mental hospital where the patients do not have civil rights to vote. It is a documentary on the meaning of choice, free will and civil rights albeit cast in a grotesque and almost absurd light.